Empathy and Trauma in Ambulance Paramedics: Navigating Human Tragedy - Saud Aziz Al Adwani; Fahad Hassan Baabdullah; Saleh Ali Saleh Alqahtani; Mubarak Hamed Almutairi; Khalid Fouad Khalid Qudus; Ahmed Abdullah Almutairi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The profession of ambulance paramedicine presents many rewarding life experiences, while simultaneously presenting healthcare practitioners with the potential for experience of repeated exposure to human tragedy. A paramedic is often the first person on scene for traumatic accidents, cardiac arrest, stabbings, or cases of child abuse. All of these situations test the professionalism of the practitioners. Pre-hospital injury and illness is often unexpected and traumatic for patients and emergency witnesses and can elicit strong emotional reactions common during trauma. Paramedics use their clinical diagnostic and technical skills to efficiently manage a wide variety of medical situations. However, regardless of the clinical skills or paramedic experience of the practitioner, outcomes for patients and witnesses may not always be good, and the person attending the incident may be left feeling markedly different than at the commencement of their shift. Surprisingly little is known about the psychological impact of service as an ambulance paramedic and how practitioners manage this stressor methods: Ambulance paramedics are trained not only in medical skills but also in caring behaviours, which are integrated into national curricula. However, various professional and personal contexts create constraints that impact their empathy and motivation. This study utilized three focus groups with 11 paramedics of differing experiences, applying Braun & Clarke’s six-phase method for thematic analysis. Three key themes emerged: ‘applying stoic professionalism as an emotional shield,’ highlighting the need to protect themselves from emotional labour; ‘compassion fatigue: when caring decays to coping,’ showing a decline towards dehumanization of patients and colleagues; and ‘disenfranchised grief: loss of human connection,’ reflecting grief from distancing themselves from normal empathetic responses. Despite the challenges, emergency medical services remain essential first responders to tragedies, facing the emotional toll of their role amid human suffering. conclusion: Most of the time, the world is a great place to live. However, occasionally, something horrible occurs, and humankind is reminded of how twisted it can be. For some, it is a horrible traffic accident, a domestic violence incident, or a drowning. Whatever the case may be, slight comfort can be taken from the fact that someone is on their way to fix it all, even if this comfort is but a tiny shade of forgiveness for the human race. Although there are many perspectives on the relationship between empathy and trauma among ambulance paramedics, the ultimate goal is to explore the factors that weaken or, more appropriately, strengthen the capacity to empathise with distressed patients. For those who have not only been trained to deal with human catastrophe but take it upon themselves to ensure that the species survives and heals, it is both a blessing and a curse .